Za kulisami współczesnej Polski – transformacje projektu quasi-publicystycznego cyklu w najnowszych powieściach Bronisława Wildsteina - Luboń, Arkadiusz (Tematy i Konteksty, 2015)
The paper deals with the most significant thematic and stylistic changes introduced by Bronisław Wildstein in three volumes published in the last decade: ’Dolina nicości’ (2008), ’Czas niedokonany’ (2011) and ’Ukryty’ (2012). The analytical approach employed allows us to treat these three novels as a link of one unwaveringly developed literary cycle. Interpretation of this cycle in the context of Wildstein’s journalistic texts – which were published at the same time – allows us to read the series as a comprehensive description of contemporary Polish reality, changes taking place in politics and society, as well as a diagnosis and predictions towards post-modern cultural trends.